Some Evolutionary Foundations for Price Level Rigidity - Gilles Saint-Paul (Center for Economic Studies and ifo Institute (CESifo), 2002)
This paper shows that price rigidity evolves in an economy populated by imperfectly rational agents who experiment with alternative rules of thumb. In the model, firms must set their prices in face of aggregate demand shocks. Their payoff depends on the level of aggregate demand, as well as on their own price and their neighbors price. The latter assumption captures local interactions. Despite the fact that the rational expectations equilibrium (REE) is characterized by a simple pricing rule that firms can easily adopt, the economy does not converge to the REE for highly autocorrelated aggregate demand shocks and a high level of local interaction. Instead, the aggregate price level exhibits rigidity, in that it does not fully react to contemporaneous aggregate demand shocks, and inertia, in that controlling to it positively depends on its past value. We show that local interactions and serial correlation of aggregate demand shocks play a key role in generating those results.
Keywords: 330; evolution; bounded rationality adaptive learning; experimentation; externalities; spillovers; local interaction; money; aggregate demand; price rigidity; rational expectations; monetary policy; macroeconomic fluctuations